Evaluation and Utility of a Family Information Table to Identify and Test Children at Risk for HIV in Kenya - Michelle Meyer, BA; Molly Elmer-DeWitt, BA; Cinthia Blat, MPH; Starley B. Shade, PhD; Ijaa Kapule, MBChB; Elizabeth Bukusi, MBChB, PhD; Craig R. Cohen, MD; Lisa Abuogi, MD (International Journal of Maternal and Child Health and AIDS, 2014)
Background: Effective strategies to identify and screen children at risk for HIV are needed. The objectives of this study were to evaluate the utilization of a family information table (FIT) to identify and test at-risk children in Kenya and identify factors associated with child testing.